GAMBARAN PERILAKU IBU DALAM PEMANFAATAN KMS DAN STATUS GIZI BADUTA DI WILAYAH KERJA PUSKESMAS LAWE PERBUNGA KECAMATAN BABUL MAKMUR KABUPATEN ACEH TENGGARA TAHUN 2015 - Rosanti Lisnawati Siagian; Etti Sudaryati; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Mother's behavior in the use Health Card consists of three domains, namely knowledge, attitudes, and actions in daily life affect nutritional status because of the KMS are monitoring the growth and development of infants. This study aims to reveal the mother's behavior in the utilization Towards Health Card and nutritional status of children in the region of Integrated Health Care Center of Lawe Perbunga Babul Makmur District of Southeast Aceh Regency in 2015 were carried out in August 2014-July 2015 with the 83 mothers who have children under two years old as respondents. This is a descriptive study with a sampling technique that is proportionate random sampling. The researes instruments were are behaviovral questionnaire and assessment for nutritional status of under two children with weight for age, height for age, and weight for height indicators. The results showed that the mother's knowledge in the use of KMS most in less category as much as 46 people (55.4%), the attitude of the mother in the use of KMS most in the category of quite as many as 43 people (51.8%), while the mother's actions in using KMS most in the category of pretty much as 55 people (66.3%), as well as nutritional status indicator of children under two years old with weight / age majority of good nutrition as much as 78 children under two years old (94.0%), nutritional status and indicators of height / age normal majority of 74 children under two years old (89.2%) and nutritional status based on indicators weight / height is a normal majority of 80 children under two years old (96.4%). Results of cross tabulation shows that knowledge and action are most lackingknowledge but action is good and sufficient. Whose actions are both more likelyto have an attitude that is less while the actions are enough to have a goodattitude. An act which did have sufficient nutritional status children under twoyears old higher than that perform good actions. Although the act of mother isgood but still found children under two years old who have poor nutritional statusand are still short. Based on these results we can conclude that although the mother's knowledge inthe use of KMS is still lacking, but the action of mothers in the use of KMS prettygood. While the mother's attitude is quite good but their actions are good enough,their attitude quite good but their actions are good. So we advised to the clinic to provide more intensive and sustained information for getting better behavioral changeand that mothers continue to monitor the growth and development of infants every month through KMS. Keywords: KMS Utilization Behavior, Nutritional Status, Under Five Children